2021
DOI: 10.1080/13678868.2021.1883937
|View full text |Cite
|
Sign up to set email alerts
|

How People Come Back to Workplaces During the Pandemic: three dimensions of intervention for new emotional performance conditions

Abstract: After months of lockdown, people returned to their workplaces filled with paradoxical emotions. The pandemic's endless duration turned the post-pandemic period into an indefinite transition that generated new coexistence conditions. This situation transformed work relationships, both physically and emotionally. Beyond cultural and economic diversities, international studies showed common patterns of emotional impact on people related to fear, hopelessness, frustration, and loneliness. The uncertainty permeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Along these lines, sadness (associated with keywords such as "disaster", "tax", "isolation") and fear emotions (related to "change", "panic", "defense") are very recurrent feelings in the period covered by the analysis. However, albeit it is evident that the COVID-19 pandemic is amplifying negative emotions and reducing positive emotions globally [65,66], there is evidence of a trusting and positive attitude by users. It is interesting to highlight that the most recurrent words are, as regards trust, "team", "management" and "top" and, as regards positive, "productivity", technology" and "learn".…”
Section: Resultsmentioning
confidence: 99%
“…Along these lines, sadness (associated with keywords such as "disaster", "tax", "isolation") and fear emotions (related to "change", "panic", "defense") are very recurrent feelings in the period covered by the analysis. However, albeit it is evident that the COVID-19 pandemic is amplifying negative emotions and reducing positive emotions globally [65,66], there is evidence of a trusting and positive attitude by users. It is interesting to highlight that the most recurrent words are, as regards trust, "team", "management" and "top" and, as regards positive, "productivity", technology" and "learn".…”
Section: Resultsmentioning
confidence: 99%
“…It points out that uncertainty is permeated in the subjective world, intimate relationship and social behavior of human beings. Three intervention levels are proposed to manage the emotional characteristics of employees after returning to work [35]. Kotera,Y., et al studies indicate that in 2019, with the prevalence of covid-19, Japanese medical workers have higher mental health problems and loneliness than the general population, and their degree of hope and self sympathy is lower than that of the general population [36].…”
Section: The Adjustment Variable Of Workplace Lonelinessmentioning
confidence: 99%
“…The public health literature provides robust evidence on how interventions can mitigate negative outcomes in the aftermath of a global public disaster ( Bauerle et al, 2020 ; Manucci, 2021 ). Previous studies have shown that cultivating and sustaining resilience is a preventive strategy for employment-related psychological burnout ( Shin et al, 2012 ; Harker et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%